Analisa Hukum Perlindungan Hak Cipta Terhadap Pembelian Buku Elektronik Secara Ilegal - Sulis Tiawati; Margo Hadi Pura (Ajudikasi : Jurnal Ilmu Hukum, 2020)
The advancement of science and technology increases over time. National development activities also make aspects of life in the community significantly improved. Similarly, in the fields of science, art, and literature that are closely related to Intellectual Property Rights. The increase in innovation technology and the development of the science sector should be supported by public awareness and market participants in understanding the importance of protecting intellectual property rights for an original product produced by a person. However, piracy of books that is still today indicates a lack of enforcement of copyright in Indonesia that harms the creator. This type of research is empirical juridical. The method of data collection used in the dissemination of questionnaires and literature studies is to study secondary legal materials related to the policy of Law No. 28 of 2014 On Copyright.The thing that affects the rise of piracy as well as from the people who become consumers, economic factors are the most chosen reason. Therefore the legal protection for copyright holders is governed by sections 99 and 113 of Law No. 28 of 2014 On Copyright, so that this piracy phenomenon can be overcome. Keywords: Law; Protection; Copyright; Electronic; Books.